Aplikasi Portofolio Dosen Untuk Pengelolaan Data Kegiatan Tridharma Perguruan Tinggi - Ziveria, Mira; Rusli, Muhammad (KALBISCIENTIA Jurnal Sains dan Teknologi, 2020)
The main task of the lecturer is to implement the tridharma of higher education. In orderto carry out the duties of the lecturer in accordance with the rules and regulations, an evaluation isneeded. Evaluation is carried out in the form of assessment and measurement of lecturer performancein a certain period of time. Performance evaluation can be seen from several processes such as theassessment of Lecturers’ Functional and Academic Position, Lecturer Certification, Lecturer Workload,and others. All lecturer performance evaluations require portfolio data that contains the activities ofthe higher education tridharma carried out by the lecturer for a certain period of time. This study aimsto build the application of lecturer portfolios for data management of tridharma activities of highereducation using the System Development Life Cycle (SDLC), system design using UML, data storage inMySQL and programming with PHP. The results of the study are an application of the lecturer portfoliowhich is expected to facilitate lecturers and universities to manage data on tridharma activities thathave been carried out by the lecturer for a certain period of time.